A method for preparing sorbitol by hydrogenating glucose
By using carbon nanotubes and bialdehyde-based cellulose to prepare the catalyst support, the problems of poor catalyst activity and poor recovery and application performance in the prior art were solved, efficient glucose conversion and sorbitol yield were achieved, and the catalyst stability was good.
Patent Information
- Application Number
- CN202411412132.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The catalyst used in the preparation of sorbitol by glucose hydrogenation has poor activity, is prone to inactivation, is not selective, and has poor recycling and application performance, which affects product quality and production operations.
The catalyst support is prepared by carbon nanotubes. The dispersion of carbon nanotubes and the uniform loading of metal active ingredients is improved by pickling and amino treatment. Then, bialdehyde-based cellulose is used as a crosslinking agent to increase the specific surface area of the support and the catalyst. stability.
The catalytic selectivity and stability of the catalyst are improved, the conversion of glucose and the yield of sorbitol are enhanced, and after multiple application, the metal active ingredient is lost less and still has excellent catalytic performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sorbitol, and particularly relates to a method for preparing sorbitol by hydrogenating glucose. Background Art
[0002] Sorbitol is a naturally occurring sugar alcohol that is widely found in many plants and fruits in nature. In the food industry, it has the functions of heat preservation, stability and taste improvement, can prevent the denaturation of carotenoids, edible fats and proteins, and extend the shelf life of food. In the pharmaceutical industry, it can be used as a matrix for bacterial biochemical characteristics tests, and also has the functions of reducing tissue edema and diuresis. In the daily chemical industry, sorbitol's hygroscopic effect makes it widely used in daily necessities such as toothpaste and cosmetics.
[0003] At present, the most commonly used production method of sorbitol is hydrogenation, which mainly adopts the catalytic hydrogenation of glucose. Specifically, glucose is hydrogenated into sorbitol using a catalyst. The traditional catalyst is mainly nickel, but it has now developed into copper, cobalt, platinum, palladium, ruthenium and other multi-catalysts;
[0004] The catalysts used in the prior art for preparing sorbitol by hydrogenation of glucose generally have poor activity, and the active components of the catalyst are easily lost and deactivated, and the selectivity during the reaction is not high. In addition, they have poor mechanical strength and are easy to break, which makes separation from the product difficult, affecting the product quality. At the same time, the breakage of the catalyst will also block the pipeline, bringing great difficulties to the production operation.
[0005] CN118084612A discloses a method for preparing sorbitol by hydrogenation of glucose, which comprises mixing a glucose aqueous solution and a catalyst, charging hydrogen and heating, and performing a hydrogenation reaction to obtain sorbitol; the specific preparation method of the catalyst comprises dissolving lanthanum nitrate hexahydrate, nickel nitrate hexahydrate or / and cobalt nitrate hexahydrate with citric acid to obtain a mixed solution; heating the mixed solution and stirring until a gel state is formed to obtain a gel mixture; drying the gel mixture, and then roasting and reducing it to obtain the catalyst;
[0006] The catalyst prepared by this method has high glucose hydrogenation activity, with the glucose conversion rate reaching more than 96.2% and the sorbitol selectivity reaching more than 97.9%; however, the catalyst has poor recycling performance. After multiple recycling and application, the glucose conversion rate and sorbitol selectivity are greatly reduced. Summary of the invention
[0007] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing sorbitol by hydrogenating glucose, the conversion rate of glucose and the selectivity of sorbitol are high, and the recovery and application performance of the catalyst is good.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] A method for preparing sorbitol by hydrogenating glucose includes preparing a catalyst carrier, loading, reducing, and hydrogenating reactions. The specific operations are as follows:
[0010] 1. Preparation of Catalyst Support
[0011] (1) Acid washing of carbon nanotubes
[0012] The carbon nanotubes are placed in a concentrated sulfuric acid solution, the temperature is raised to 82-87°C, and ball milling is performed. The ball milling time is 27-34 minutes, the ball milling speed is 285-312 rpm, and after the ball milling is completed, the solution is allowed to stand for 1.8-2.3 hours. After the standing, the solution is washed and dried at 78-82°C for 11-13 hours to obtain acid-washed carbon nanotubes.
[0013] The carbon nanotubes have a particle size of 260-290 nm and a specific surface area of 410-430 m 2 / g;
[0014] The mass ratio of the carbon nanotubes to the concentrated sulfuric acid solution is 8.3-8.8:60-65;
[0015] The mass concentration of the concentrated sulfuric acid solution is 70-74%;
[0016] (2) Amination of carbon nanotubes
[0017] The acid-washed carbon nanotubes are placed in an ethanol solution, glycerol monooleate and polyethylene glycol octylphenyl ether are added, the temperature is raised to 58-62° C. for ball milling, the ball milling time is 33-37 minutes, the ball milling speed is 204-215 rpm, the ball-to-material ratio is 3-5:1, and after the ball milling is completed, a carbon nanotube mixed solution is obtained; ethylenediamine, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and triethanolamine dodecylsulfate are added to the ethanol solution, and ultrasonic treatment is performed, the ultrasonic time is 13-18 minutes, the ultrasonic power is 212-225W, and the ultrasonic frequency is 14-17kHz. After the ultrasonic treatment is completed, an amination reagent is obtained;
[0018] The mass concentration of the ethanol solution is 33-36%;
[0019] In the carbon nanotube mixed solution, the mass ratio of the acid-washed carbon nanotubes, the ethanol solution, the glycerol monooleate, and the polyethylene glycol octylphenyl ether is 10.6-11.1:57-62:0.6-0.8:0.2-0.6;
[0020] In the aminating agent, the mass ratio of the ethanol solution, ethylenediamine, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and triethanolamine dodecyl sulfate is 47-53:0.4-0.6:0.7-0.9:0.3-0.5;
[0021] Slowly add the aminating agent to the carbon nanotube mixture, control the addition rate to be 1.7-2.3 g / min, stir and heat the mixture while adding, control the stirring speed to be 243-256 rpm, and the heating rate to be 2.8-3.2° C. / min. Stop heating when the addition is completed, keep warm and stir at 315-326 rpm for 8.3-8.5 h. After the stirring is completed, wait until the mixture is cooled to room temperature naturally, filter, wash, and dry to obtain aminating carbon nanotubes;
[0022] The mass ratio of the carbon nanotube mixed solution to the aminating agent is 71.4-72.2:51.5-52.0;
[0023] (3) Stabilization
[0024] Add hydrochloric acid solution to the reaction container, then add ammoniated carbon nanotubes and β-cyclodextrin, stir evenly, raise the temperature to 60-64°C, stir for 27-34 minutes, and stir at a speed of 390-410 rpm. After the stirring is completed, add dialdehyde cellulose, raise the temperature to 88-92°C at a rate of 0.4-0.6°C / min, and perform ultrasonic treatment. The ultrasonic time is 14-16 minutes, the ultrasonic power is 107-113W, and the ultrasonic frequency is 28-32kHz. After the ultrasonic treatment is completed, stir and react at 302-318 rpm for 2.4-2.6 hours. After the stirring reaction is completed, add 7.8-8.2wt% sodium hydroxide solution, adjust the pH to 11.3-11.6, and continue stirring for 1.4-1.7 hours. After the stirring is completed, filter, wash, and dry to obtain a catalyst carrier.
[0025] The mass concentration of the hydrochloric acid solution is 5.0-5.5%;
[0026] The mass volume ratio of the hydrochloric acid solution, ammoniated carbon nanotubes, β-cyclodextrin, and dialdehyde cellulose is 480-520 mL: 6.3-6.g: 1.3-1.5g: 2.0-2.4g;
[0027] The preparation method of dialdehyde cellulose comprises placing cellulose in deionized water, stirring evenly, adding sodium periodate, raising the temperature to 52-55° C., stirring for 3.8-4.2 hours under light-proof conditions, and stirring at a speed of 344-355 rpm. After the reaction is completed, adding ethylene glycol and continuing stirring for 8-12 minutes. After the stirring is completed, filtering, washing, and drying to obtain dialdehyde cellulose.
[0028] The particle size of the cellulose is 310-330 nm;
[0029] The mass ratio of cellulose, deionized water, sodium periodate and ethylene glycol is 4.8-5.2:195-206:6.4-6.6:4.3-4.8;
[0030] 2. Load
[0031] Nickel nitrate hexahydrate, lanthanum nitrate hexahydrate and deionized water are mixed, stirred evenly, and then a catalyst carrier is added for homogenization. The homogenization time is 4.5-5.5 minutes, the homogenization pressure is 4.8-5.3 MPa, and the homogenization times are 2 times. After the homogenization treatment is completed, the temperature is increased to 58-63° C. and stirred at 480-520 rpm. After the stirring is completed, the catalyst is filtered, washed and dried to obtain a catalyst.
[0032] The mass ratio of the nickel nitrate hexahydrate, the lanthanum nitrate hexahydrate, the deionized water and the catalyst carrier is 3.04-3.15:1.76-1.90:78-83:1.0-1.3.
[0033] 3. Restore
[0034] The catalyst was reduced in a reducing atmosphere of hydrogen. The temperature was first raised to 206-214°C at a rate of 4.8-5.2°C / min, and kept warm for 13-17 minutes. The temperature was then raised to 355-365°C at a rate of 2.8-3.2°C / min, and kept warm for 28-32 minutes. The temperature was then raised to 400-410°C at a rate of 1.7-2.0°C / min, and kept warm for 3.8-4.3 hours. After the insulation was completed, the catalyst was naturally cooled to room temperature to obtain a reduced catalyst.
[0035] 4. Hydrogenation reaction
[0036] Add glucose aqueous solution to the reaction container, then add reduction catalyst, stir evenly, seal the reaction container, replace the gas in the reaction container with hydrogen 3 times, introduce hydrogen, control the pressure to 3.0-3.4MPa, stir at 640-660rpm, heat to 117-122℃ at 4.0-4.5℃ / min, keep warm for 4.3-4.7h, cool to room temperature after the reaction, collect liquid product, and take samples for analysis;
[0037] The mass concentration of the glucose aqueous solution is 18-22%;
[0038] The mass ratio of the glucose aqueous solution to the reduction catalyst is 450-500:4.7-5.0.
[0039] Compared with the prior art, the present invention has achieved the following effects:
[0040] 1. The present invention adopts carbon nanotubes to prepare catalyst carriers. First, the carbon nanotubes are acid-washed to remove impurities in the pores of the carbon nanotubes. Then, the carbon nanotubes are aminated to load more amino groups on the surface of the carbon nanotubes, which promotes the dispersion of the carbon nanotubes, ensures the uniform loading of metal active components, and better exerts their catalytic activity. Then, dialdehyde cellulose is used as a cross-linking agent to cross-link the aminated carbon nanotubes with β-cyclodextrin, thereby increasing the specific surface area of the carrier, improving the catalytic selectivity of the catalyst, and having good stability and good solid loading capacity for metal active components, thereby avoiding the loss of metal active components during the reaction. In addition, the catalyst has more hydrophilic groups such as amino, hydroxyl, and carboxyl groups, which have good binding properties with the hydroxyl groups of glucose and good compatibility with reactants, thereby improving the catalytic performance and catalytic stability of the catalyst, thereby promoting the hydrogenation reaction, improving the reaction rate of glucose, and enhancing the recycling performance of the catalyst. After multiple applications, the loss of metal active components is less, and the catalyst still has excellent catalytic performance, thereby ensuring the conversion rate of glucose and the yield of sorbitol.
[0041] 2. Sorbitol was prepared by the method of the present invention. After sampling and analysis of the liquid product, the yield of sorbitol was 92.46-93.87%, and the conversion rate of glucose was 98.73-100%;
[0042] 3. The catalyst prepared by the present invention was recycled and reused. When it was used for the 30th time, the yield of sorbitol was 88.30-90.68%, and the conversion rate of glucose was 95.18-97.11%. DETAILED DESCRIPTION
[0043] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0044] Example 1
[0045] 1. Preparation of Catalyst Support
[0046] (1) Acid washing of carbon nanotubes
[0047] 8.5 g of carbon nanotubes were placed in 62 g of 72 wt% concentrated sulfuric acid solution, the temperature was raised to 85°C, and ball milling was performed. The ball milling time was 30 min, the ball milling speed was 300 rpm, and after the ball milling was completed, it was allowed to stand for 2.0 h. After the standing, it was washed and dried at 80°C for 12 h to obtain acid-washed carbon nanotubes;
[0048] The carbon nanotubes have a particle size of 270 nm and a specific surface area of 420 m 2 / g;
[0049] (2) Amination of carbon nanotubes
[0050] 10.8g of acid-washed carbon nanotubes were placed in 60g of 35wt% ethanol solution, 0.7g of glycerol monooleate and 0.4g of polyethylene glycol octylphenyl ether were added, the temperature was raised to 60°C for ball milling, the ball milling time was 35min, the ball milling speed was 210rpm, the ball-to-material ratio was 4:1, and after the ball milling was completed, a carbon nanotube mixed solution was obtained; 0.5g of ethylenediamine, 0.8g of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 0.4g of triethanolamine dodecylsulfate were added to 50g of 35wt% ethanol solution, and ultrasonic treatment was performed, the ultrasonic time was 15min, the ultrasonic power was 220W, and the ultrasonic frequency was 15kHz. After the ultrasonic treatment, an aminating reagent was obtained;
[0051] Slowly add 51.7g of aminating agent to 71.9g of the carbon nanotube mixed solution, control the addition rate to 2.0g / min, stir and heat while adding, control the stirring speed to 250rpm, and the heating rate to 3.0℃ / min. Stop heating when the addition is completed, keep warm and stir at 320rpm for 8.4h. After stirring, wait until the temperature naturally drops to room temperature, filter, wash and dry to obtain aminating carbon nanotubes;
[0052] (3) Stabilization
[0053] Add 500mL of 5.2wt% hydrochloric acid solution to the reaction container, then add 6.5g of ammoniated carbon nanotubes and 1.4g of β-cyclodextrin, stir evenly, raise the temperature to 62°C, stir for 30min, and stir at a speed of 400rpm. After stirring, add 2.2g of dialdehyde cellulose, raise the temperature to 90°C at a rate of 0.5°C / min, and perform ultrasonic treatment. The ultrasonic time is 15min, the ultrasonic power is 110W, and the ultrasonic frequency is 30kHz. After the ultrasonic treatment is completed, stir and react at 310rpm for 2.5h. After the stirring reaction is completed, add 8.0wt% sodium hydroxide solution, adjust the pH to 11.5, and continue stirring for 1.5h. After the stirring is completed, filter, wash, and dry to obtain a catalyst carrier.
[0054] The preparation method of the dialdehyde cellulose comprises the following steps: placing 5.0 g of cellulose in 200 g of deionized water, stirring evenly, adding 6.5 g of sodium periodate, raising the temperature to 53° C., stirring for 4.0 h in a light-proof condition, and stirring at a speed of 350 rpm. After the reaction is completed, adding 4.5 g of ethylene glycol and stirring for 10 min. After the stirring is completed, filtering, washing, and drying to obtain the dialdehyde cellulose.
[0055] The particle size of the cellulose is 320 nm.
[0056] 2. Load
[0057] Mix 3.10g nickel nitrate hexahydrate, 1.82g lanthanum nitrate hexahydrate and 80g deionized water, stir evenly, add 1.1g catalyst carrier for homogenization, the homogenization time is 5min, the homogenization pressure is 5.0MPa, the homogenization times are 2 times. After the homogenization treatment is completed, increase the temperature to 60°C, stir at 500rpm, filter, wash and dry after stirring to obtain the catalyst.
[0058] 3. Restore
[0059] The catalyst was reduced in a reducing atmosphere of hydrogen. The temperature was first raised to 210°C at a rate of 5.0°C / min and kept for 15 minutes. The temperature was then raised to 360°C at a rate of 3.0°C / min and kept for 30 minutes. The temperature was then raised to 405°C at a rate of 1.8°C / min and kept for 4.0 hours. After the insulation was completed, the catalyst was naturally cooled to room temperature to obtain a reduced catalyst.
[0060] 4. Hydrogenation reaction
[0061] Add 490g of 20wt% glucose aqueous solution to the reaction vessel, then add 4.8g of reducing catalyst, stir evenly, seal the reaction vessel, replace the gas in the reaction vessel with hydrogen 3 times, introduce hydrogen, control the pressure at 3.2MPa, and stir at 650rpm. Raise the temperature to 120℃ at a rate of 4.2℃ / min, and keep the reaction for 4.5h. After the reaction is completed, cool to room temperature, collect the liquid product, and take samples for analysis.
[0062] Sorbitol was prepared by the method of Example 1. After sampling and analysis of the liquid product, the yield of sorbitol was 93.87% and the conversion rate of glucose was 100%.
[0063] The catalyst of Example 1 was recycled and reused 30 times, and the catalyst was recycled after each hydrogenation reaction step. At the 30th time of use, the yield of sorbitol was 90.68%, and the conversion rate of glucose was 97.11%.
[0064] Example 2
[0065] 1. Preparation of Catalyst Support
[0066] (1) Acid washing of carbon nanotubes
[0067] 8.3 g of carbon nanotubes were placed in 60 g of 70 wt% concentrated sulfuric acid solution, the temperature was raised to 82°C, and ball milling was performed. The ball milling time was 27 min, the ball milling speed was 285 rpm, and after the ball milling was completed, it was allowed to stand for 1.8 h. After the standing, it was washed and dried at 78°C for 13 h to obtain acid-washed carbon nanotubes.
[0068] The carbon nanotubes have a particle size of 260 nm and a specific surface area of 410 m 2 / g;
[0069] (2) Amination of carbon nanotubes
[0070] 10.6 g of acid-washed carbon nanotubes were placed in 57 g of 33 wt% ethanol solution, 0.6 g of glycerol monooleate and 0.2 g of polyethylene glycol octylphenyl ether were added, the temperature was raised to 58 ° C for ball milling, the ball milling time was 33 min, the ball milling speed was 204 rpm, the ball-to-material ratio was 3:1, and after the ball milling was completed, a carbon nanotube mixed solution was obtained; 0.4 g of ethylenediamine, 0.7 g of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 0.3 g of triethanolamine dodecyl sulfate were added to 47 g of 33 wt% ethanol solution, and ultrasonic treatment was performed, the ultrasonic time was 13 min, the ultrasonic power was 212 W, and the ultrasonic frequency was 14 kHz. After the ultrasonic treatment, an aminating reagent was obtained;
[0071] Slowly add 51.5g of aminating agent to 71.4g of the carbon nanotube mixed solution, control the addition rate to 1.7g / min, stir and heat while adding, control the stirring speed to 243rpm, and the heating rate to 2.8℃ / min. Stop heating when the addition is completed, keep warm and stir at 315rpm for 8.3h. After the stirring is completed, wait until it is naturally cooled to room temperature, filter, wash and dry to obtain aminating carbon nanotubes;
[0072] (3) Stabilization
[0073] Add 480mL of 5.0wt% hydrochloric acid solution to the reaction container, then add 6.3g of ammoniated carbon nanotubes and 1.3g of β-cyclodextrin, stir evenly, raise the temperature to 60°C, stir for 27min, and stir at a speed of 390rpm. After stirring, add 2.0g of dialdehyde cellulose, raise the temperature to 88°C at a rate of 0.4°C / min, and perform ultrasonic treatment. The ultrasonic time is 14min, the ultrasonic power is 107W, and the ultrasonic frequency is 28kHz. After the ultrasonic treatment is completed, stir and react at 302rpm for 2.4h. After the stirring reaction is completed, add 7.8wt% sodium hydroxide solution, adjust the pH to 11.3, and continue stirring for 1.4h. After the stirring is completed, filter, wash, and dry to obtain a catalyst carrier.
[0074] The preparation method of the dialdehyde cellulose is as follows: 4.8 g of cellulose is placed in 195 g of deionized water, and after being stirred evenly, 6.4 g of sodium periodate is added, the temperature is raised to 52° C., and the reaction is stirred for 3.8 hours under light-proof conditions, and the stirring speed is 344 rpm. After the reaction is completed, 4.3 g of ethylene glycol is added and the stirring is continued for 8 minutes. After the stirring is completed, the dialdehyde cellulose is filtered, washed, and dried to obtain the dialdehyde cellulose;
[0075] The particle size of the cellulose is 310 nm.
[0076] 2. Load
[0077] 3.04 g of nickel nitrate hexahydrate, 1.76 g of lanthanum nitrate hexahydrate and 78 g of deionized water were mixed and stirred evenly, and then 1.0 g of catalyst carrier was added for homogenization. The homogenization time was 4.5 min, the homogenization pressure was 5.3 MPa, and the homogenization times were 2 times. After the homogenization treatment was completed, the temperature was increased to 58°C and stirred at 480 rpm. After the stirring was completed, the catalyst was filtered, washed and dried.
[0078] 3. Restore
[0079] The catalyst was reduced in a reducing atmosphere of hydrogen. The temperature was first raised to 206°C at a rate of 4.8°C / min and kept for 13 min. The temperature was then raised to 355°C at a rate of 2.8°C / min and kept for 28 min. The temperature was then raised to 400°C at a rate of 1.7°C / min and kept for 3.8 h. After the insulation was completed, the catalyst was naturally cooled to room temperature to obtain a reduced catalyst.
[0080] 4. Hydrogenation reaction
[0081] Add 450g of 18wt% glucose aqueous solution to the reaction vessel, then add 4.7g of reducing catalyst, stir evenly, seal the reaction vessel, replace the gas in the reaction vessel with hydrogen 3 times, introduce hydrogen, control the pressure to 3.0MPa, and the stirring speed to 640rpm. Raise the temperature to 117°C at a rate of 4.0°C / min, and keep the reaction for 4.7h. After the reaction is completed, cool to room temperature, collect the liquid product, and take samples for analysis.
[0082] Sorbitol was prepared by the method of Example 2. After sampling and analysis of the liquid product, the yield of sorbitol was 92.46%, and the conversion rate of glucose was 98.73%;
[0083] The catalyst of Example 2 was recycled and reused 30 times, and the catalyst was recycled after each hydrogenation reaction step. At the 30th time of use, the yield of sorbitol was 88.30%, and the conversion rate of glucose was 95.18%.
[0084] Example 3
[0085] 1. Preparation of Catalyst Support
[0086] (1) Acid washing of carbon nanotubes
[0087] 8.8 g of carbon nanotubes were placed in 65 g of 74 wt% concentrated sulfuric acid solution, the temperature was raised to 87°C, and ball milling was performed. The ball milling time was 34 min, the ball milling speed was 312 rpm, and after the ball milling was completed, it was allowed to stand for 2.3 h. After the standing, it was washed and dried at 82°C for 11 h to obtain acid-washed carbon nanotubes;
[0088] The carbon nanotubes have a particle size of 290 nm and a specific surface area of 430 m 2 / g;
[0089] (2) Amination of carbon nanotubes
[0090] 11.1g of acid-washed carbon nanotubes were placed in 62g of 36wt% ethanol solution, 0.8g of glycerol monooleate and 0.6g of polyethylene glycol octylphenyl ether were added, the temperature was raised to 62°C for ball milling, the ball milling time was 37min, the ball milling speed was 215rpm, the ball-to-material ratio was 5:1, and after the ball milling, a carbon nanotube mixed solution was obtained; 0.6g of ethylenediamine, 0.9g of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and 0.5g of triethanolamine dodecylsulfate were added to 53g of 36wt% ethanol solution, and ultrasonic treatment was carried out, the ultrasonic time was 18min, the ultrasonic power was 225W, and the ultrasonic frequency was 17kHz. After the ultrasonic treatment, an aminating reagent was obtained;
[0091] Slowly add 52.0g of aminating agent to 72.2g of the carbon nanotube mixed solution, control the addition rate to 2.3g / min, stir and heat while adding, control the stirring speed to 256rpm, and the heating rate to 3.2℃ / min. Stop heating when the addition is completed, keep warm and stir at 326rpm for 8.5h. After the stirring is completed, wait until it is naturally cooled to room temperature, filter, wash and dry to obtain aminating carbon nanotubes;
[0092] (3) Stabilization
[0093] Add 520mL of 5.5wt% hydrochloric acid solution to the reaction container, then add 6.8g of ammoniated carbon nanotubes and 1.5g of β-cyclodextrin, stir evenly, raise the temperature to 64°C, stir for 34min, and stir at a speed of 410rpm. After stirring, add 2.4g of dialdehyde cellulose, raise the temperature to 92°C at a rate of 0.6°C / min, and perform ultrasonic treatment. The ultrasonic time is 16min, the ultrasonic power is 113W, and the ultrasonic frequency is 32kHz. After the ultrasonic treatment is completed, stir and react at 318rpm for 2.6h. After the stirring reaction is completed, add 8.2wt% sodium hydroxide solution, adjust the pH to 11.6, and continue stirring for 1.7h. After the stirring is completed, filter, wash, and dry to obtain a catalyst carrier.
[0094] The preparation method of the dialdehyde cellulose is as follows: 5.2 g of cellulose is placed in 206 g of deionized water, and after stirring evenly, 6.6 g of sodium periodate is added, the temperature is raised to 55° C., and the reaction is stirred for 4.2 hours under light-proof conditions, and the stirring speed is 355 rpm. After the reaction is completed, 4.8 g of ethylene glycol is added and the stirring is continued for 12 minutes. After the stirring is completed, the dialdehyde cellulose is filtered, washed, and dried to obtain the dialdehyde cellulose;
[0095] The particle size of the cellulose is 330 nm.
[0096] 2. Load
[0097] 3.15g of nickel nitrate hexahydrate, 1.90g of lanthanum nitrate hexahydrate and 83g of deionized water were mixed and stirred evenly, and then 1.3g of catalyst carrier was added for homogenization. The homogenization time was 5.5min, the homogenization pressure was 4.8MPa, and the homogenization times were 2 times. After the homogenization treatment was completed, the temperature was increased to 63°C and stirred at 520rpm. After the stirring was completed, the catalyst was filtered, washed and dried.
[0098] 3. Restore
[0099] The catalyst was reduced in a reducing atmosphere of hydrogen. The temperature was first raised to 214°C at a rate of 5.2°C / min and kept for 17 min. The temperature was then raised to 365°C at a rate of 3.2°C / min and kept for 32 min. The temperature was then raised to 410°C at a rate of 2.0°C / min and kept for 4.3 h. After the insulation was completed, the catalyst was naturally cooled to room temperature to obtain a reduced catalyst.
[0100] 4. Hydrogenation reaction
[0101] Add 500 g of 22 wt% glucose aqueous solution to the reaction vessel, then add 5.0 g of reducing catalyst, stir evenly, seal the reaction vessel, replace the gas in the reaction vessel with hydrogen 3 times, introduce hydrogen, control the pressure at 3.4 MPa, and stir at 660 rpm. Raise the temperature to 122 °C at a rate of 4.5 °C / min, and keep the reaction for 4.3 h. After the reaction is completed, cool to room temperature, collect the liquid product, and take samples for analysis.
[0102] Sorbitol was prepared by the method of Example 3. After sampling and analysis of the liquid product, the yield of sorbitol was 93.25%, and the conversion rate of glucose was 99.21%;
[0103] The catalyst of Example 3 was recycled and reused 30 times, and the catalyst was recycled after each hydrogenation reaction step. At the 30th time of use, the yield of sorbitol was 89.61%, and the conversion rate of glucose was 96.04%.
[0104] Comparative Example 1
[0105] Based on Example 1, the changes are as follows:
[0106] The carbon nanotube ammoniation step is omitted, and in the stabilization step, an equal amount of acid-washed carbon nanotubes is used to replace the ammonated nanotubes; an equal amount of dialdehyde cellulose is replaced by cellulose without any treatment;
[0107] The rest of the operations are the same.
[0108] Sorbitol was prepared by the method of Comparative Example 1. After sampling and analysis of the liquid product, the yield of sorbitol was 81.62% and the conversion rate of glucose was 87.54%;
[0109] The catalyst of Comparative Example 1 was recycled and reused 30 times, and the catalyst was recycled after each hydrogenation reaction step. At the 30th time of use, the yield of sorbitol was 67.17%, and the conversion rate of glucose was 73.45%.
[0110] Comparative Example 2
[0111] Based on Example 1, the changes are as follows: the stabilization step is omitted; in the loading step, the catalyst carrier is replaced with an equal amount of ammoniated carbon nanotubes;
[0112] The rest of the operations are the same.
[0113] Sorbitol was prepared by the method of Comparative Example 1. After sampling and analysis of the liquid product, the yield of sorbitol was 84.09% and the conversion rate of glucose was 90.22%;
[0114] The catalyst of Comparative Example 2 was recycled and reused 30 times, and the catalyst was recycled after each hydrogenation reaction step. At the 30th time of use, the yield of sorbitol was 70.72%, and the conversion rate of glucose was 76.69%.
[0115] When the catalysts prepared in Examples 1-3 and Comparative Examples 1-2 are recovered and reused, the catalyst recovery method is as follows: the liquid product prepared in the hydrogenation reaction step is cooled, and then vacuum filtered to obtain a filter cake, the filter cake is washed with deionized water for 4 times, and dried at 115°C. After drying, it is naturally cooled to room temperature, heated to 320°C at a rate of 3.0°C / min, and calcined at 320°C for 4.0h, the calcination atmosphere is oxygen, and after the calcination, it is naturally restored to room temperature, placed in a hydrogen atmosphere for reduction, the heating rate is 3.0°C / min, the temperature is raised to 380°C and kept warm for 4.0h, and after the reduction is completed, it is naturally cooled to room temperature to obtain a regenerated catalyst; the number of recovery and reuse is 30 times, and the catalyst is recovered after each hydrogenation reaction step; at the 30th application, the conversion rate of glucose and the yield of sorbitol are measured.
[0116] The present invention adopts carbon nanotubes to prepare catalyst carriers. First, the carbon nanotubes are acid-washed to remove impurities in the pores of the carbon nanotubes. Then, the carbon nanotubes are aminated to load more amino groups on the surface of the carbon nanotubes, which promotes the dispersion of the carbon nanotubes, ensures the uniform loading of metal active components, and better exerts the catalytic activity. Then, dialdehyde cellulose is used as a crosslinking agent to crosslink the aminated carbon nanotubes with beta-cyclodextrin, thereby increasing the specific surface area of the carrier, improving the catalytic selectivity of the catalyst, and having good stability and good solid loading capacity for the metal active components, thereby avoiding the loss of the metal active components during the reaction. The catalyst has more hydrophilic groups such as amino, hydroxyl, and carboxyl groups, has good binding performance with the hydroxyl group of glucose, has good compatibility with reactants, improves the catalytic performance and catalytic stability of the catalyst, and further promotes the progress of hydrogenation reaction, improves the reaction rate of glucose, and enhances the recycling performance of the catalyst. After multiple applications, the metal active components are less lost, and the catalyst still has excellent catalytic performance, thereby ensuring the conversion rate of glucose and the yield of sorbitol.
[0117] In Comparative Example 1, the ammoniation step of carbon nanotubes is omitted, and the carbon nanotubes are easy to aggregate. In the stabilization step, cellulose is not formaldehyded, and the carbon nanotubes, β-cyclodextrin and cellulose are in a serious aggregation state, which affects the adsorption of metal active components, weakens the catalytic performance of the catalyst, affects the reaction, and during the reaction, a large amount of metal active components are lost, the catalytic performance is sharply weakened, and the conversion rate and yield are significantly reduced, and its final recycling performance is poor.
[0118] Comparative Example 2 only uses ammoniated carbon nanotubes as catalyst carriers and omits the stabilization step. Ammoniated carbon nanotubes can load metal active ingredients, but compared with the cross-linked catalyst carrier, they have poor adsorption performance and unstable catalytic performance. As the reaction proceeds, the metal active ingredients are gradually lost, affecting the reaction rate of glucose, thereby reducing the conversion rate and affecting the product yield. There is also the problem of poor recycling performance.
[0119] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.
[0120] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing sorbitol by hydrogenating glucose, characterized in that: Including preparation of catalyst carrier, loading, reduction, hydrogenation reaction; The preparation of the catalyst carrier comprises the steps of acid washing of carbon nanotubes, ammoniation of carbon nanotubes and stabilization; The carbon nanotube pickling step comprises placing the carbon nanotube in a concentrated sulfuric acid solution, raising the temperature to 82-87° C., and performing ball milling treatment. The ball milling time is 27-34 minutes, the ball milling speed is 285-312 rpm, and after the ball milling is completed, the carbon nanotube is allowed to stand for 1.8-2.3 hours. After the standing is completed, the carbon nanotube is washed and dried at 78-82° C. for 11-13 hours to obtain the pickled carbon nanotube. The carbon nanotube ammoniation step comprises: slowly adding an ammoniation agent to the carbon nanotube mixture, controlling the addition rate to be 1.7-2.3 g / min, stirring and heating the mixture while adding, controlling the stirring speed to be 243-256 rpm, and the heating rate to be 2.8-3.2° C. / min, stopping heating when the addition is completed, and stirring at 315-326 rpm for 8.3-8.5 hours. After the stirring is completed, the mixture is cooled to room temperature naturally, filtered, washed, and dried to obtain ammoniation carbon nanotubes; The carbon nanotube mixed solution is prepared by placing acid-washed carbon nanotubes in an ethanol solution, adding glycerol monooleate and polyethylene glycol octylphenyl ether, raising the temperature to 58-62° C. and performing ball milling. The aminating agent is prepared by adding ethylenediamine, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and triethanolamine dodecylsulfate to an ethanol solution and performing ultrasonic treatment; The stabilization step comprises: adding a hydrochloric acid solution to a reaction container, then adding ammoniated carbon nanotubes and β-cyclodextrin, stirring evenly, and performing a stirring reaction. After the first stirring reaction, adding dialdehyde cellulose, heating to 88-92° C. at a rate of 0.4-0.6° C. / min, performing ultrasonic treatment, and performing a second stirring reaction after the ultrasonic treatment. After the second stirring reaction, adding 7.8-8.2wt% sodium hydroxide solution, adjusting the pH to 11.3-11.6, continuing stirring for 1.4-1.7h, filtering, washing, and drying after the stirring, to obtain a catalyst carrier; The dialdehyde cellulose is prepared by placing cellulose in deionized water and adding sodium periodate for oxidation; The loading step comprises mixing nickel nitrate hexahydrate, lanthanum nitrate hexahydrate and deionized water, stirring evenly, adding a catalyst carrier for homogenization, raising the temperature to 58-63° C. after the homogenization, stirring at 480-520 rpm, filtering, washing and drying after the stirring, and obtaining a catalyst; The reduction step comprises reducing the catalyst in a reducing atmosphere of hydrogen, firstly heating the temperature to 206-214°C at a rate of 4.8-5.2°C / min, keeping the temperature for 13-17min, then heating the temperature to 355-365°C at a rate of 2.8-3.2°C / min, keeping the temperature for 28-32min, then heating the temperature to 400-410°C at a rate of 1.7-2.0°C / min, keeping the temperature for 3.8-4.3h, and after the end of the keeping temperature, naturally cooling to room temperature to obtain a reduced catalyst; The hydrogenation reaction step comprises mixing the glucose aqueous solution and the reduction catalyst, and reacting them in a sealed state under a hydrogen atmosphere; The mass concentration of the glucose aqueous solution is 18-22%; The mass ratio of the glucose aqueous solution to the reduction catalyst is 450-500:4.7-5.
0.
2. The method for preparing sorbitol by hydrogenating glucose according to claim 1, characterized in that: In the carbon nanotube pickling step, the carbon nanotube has a particle size of 260-290 nm and a specific surface area of 410-430 m 2 / g; The mass ratio of the carbon nanotubes to the concentrated sulfuric acid solution is 8.3-8.8:60-65; The mass concentration of the concentrated sulfuric acid solution is 70-74%.
3. The method for preparing sorbitol by hydrogenating glucose according to claim 1, characterized in that: In the carbon nanotube amination step, the mass ratio of the carbon nanotube mixed solution to the amination reagent is 71.4-72.2:51.5-52.0; The preparation method of the carbon nanotube mixed solution is as follows: placing the acid-washed carbon nanotubes in an ethanol solution, adding glycerol monooleate and polyethylene glycol octylphenyl ether, raising the temperature to 58-62° C. for ball milling, the ball milling time is 33-37 min, the ball milling speed is 204-215 rpm, the ball-to-material ratio is 3-5:1, and after the ball milling is completed, the carbon nanotube mixed solution is obtained; The preparation method of the aminating agent comprises the following steps: adding ethylenediamine, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and triethanolamine dodecylsulfate into an ethanol solution, and performing ultrasonic treatment, wherein the ultrasonic treatment time is 13-18 minutes, the ultrasonic power is 212-225 W, and the ultrasonic frequency is 14-17 kHz. After the ultrasonic treatment is completed, the aminating agent is obtained.
4. The method for preparing sorbitol by hydrogenating glucose according to claim 3, characterized in that: The mass concentration of the ethanol solution is 33-36%; In the method for preparing the carbon nanotube mixed solution, the mass ratio of the acid-washed carbon nanotubes, the ethanol solution, the glycerol monooleate, and the polyethylene glycol octylphenyl ether is 10.6-11.1:57-62:0.6-0.8:0.2-0.6; In the preparation method of the aminating agent, the mass ratio of the ethanol solution, ethylenediamine, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane and triethanolamine dodecyl sulfate is 47-53:0.4-0.6:0.7-0.9:0.3-0.
5.
5. The method for preparing sorbitol by hydrogenating glucose according to claim 1, characterized in that: In the stabilization step, the temperature of the first stirring reaction is 60-64°C, the time is 27-34min, and the stirring speed is 390-410rpm; The ultrasonic treatment comprises an ultrasonic time of 14-16 min, an ultrasonic power of 107-113 W, and an ultrasonic frequency of 28-32 kHz; The secondary stirring reaction has a stirring speed of 302-318 rpm and a stirring time of 2.4-2.6 h.
6. The method for preparing sorbitol by hydrogenating glucose according to claim 1, characterized in that: The mass concentration of the hydrochloric acid solution is 5.0-5.5%; The volume mass ratio of the hydrochloric acid solution, ammoniated carbon nanotubes, β-cyclodextrin, and dialdehyde cellulose is 480-520 mL: 6.3-6.g: 1.3-1.5g: 2.0-2.4g; The mass concentration of the sodium hydroxide solution is 7.8-8.2%.
7. The method for preparing sorbitol by hydrogenating glucose according to claim 1, characterized in that: The preparation method of dialdehyde cellulose comprises placing cellulose in deionized water, stirring evenly, adding sodium periodate, raising the temperature to 52-55° C., stirring for 3.8-4.2 hours under light-proof conditions, and stirring at a speed of 344-355 rpm. After the reaction is completed, adding ethylene glycol and continuing stirring for 8-12 minutes. After the stirring is completed, filtering, washing, and drying to obtain dialdehyde cellulose. The particle size of the cellulose is 310-330 nm; The mass ratio of the cellulose, deionized water, sodium periodate and ethylene glycol is 4.8-5.2:195-206:6.4-6.6:4.3-4.
8.
8. The method for preparing sorbitol by hydrogenating glucose according to claim 1, characterized in that: In the loading step, the homogenization time is 4.5-5.5 min, the homogenization pressure is 4.8-5.3 MPa, and the homogenization times are 2 times; The mass ratio of the nickel nitrate hexahydrate, the lanthanum nitrate hexahydrate, the deionized water and the catalyst carrier is 3.04-3.15:1.76-1.90:78-83:1.0-1.
3.
9. The method for preparing sorbitol by hydrogenating glucose according to claim 1, characterized in that: The hydrogenation reaction step is to add a glucose aqueous solution into a reaction container, then add a reduction catalyst, stir evenly, seal the reaction container, replace the gas in the reaction container with hydrogen for 3 times, introduce hydrogen, control the pressure to 3.0-3.4MPa, stir at a speed of 640-660rpm, heat to 117-122°C at a rate of 4.0-4.5°C / min, keep warm for 4.3-4.7h, cool to room temperature after the reaction is completed, collect liquid products, and take samples for analysis.
Citation Information
Patent Citations
Method for preparing sorbitol through glucose hydrogenation
CN118084612A
Cyclodextrin-carbon nano tube derivatives and preparation method thereof
CN101264881A
Novel Ru / CNTs catalyst used for preparing sorbitol through glucose hydrogenation, and preparation and application method thereof
CN104107691A